PENGARUH KOMPETENSI PROFESIONAL GURU, EFIKASI DIRI, DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU SMPN 1 KERINCI KANAN KABUPATEN SIAK - Alies Choiron; Machasin -; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study to obtain valid and reliable information about the influence of professional competence of teachers on teacher performance in SMPN 1 Kerinci Kanan Kabupaten Siak, effects of self-efficacy on teacher performance in SMPN 1 Kerinci Kanan Kabupaten Siak, interpersonal communication influence on teacher performance in SMPN 1 Kerinci Kanan Kabupaten Siak, effect of teachers' professional competence, self-efficacy and interpersonal communication together on teacher performance in SMPN 1 Kerinci Kanan Kabupaten Siak. The study population was all teachers in SMPN 1 Kerinci Kanan Kabupaten Siak totaling 34 people. In this study used census method, the entire population sampled that all teachers in SMPN 1 Kerinci Kanan Kabupaten Siak.The results showed that there are significant professional competence of teachers on teacher performance SMPN 1 Kerinci Kanan Kabupaten Siak, although the effect is not as big as the effect of which is owned by self-efficacy, there is an influence on the performance of teachers' self-efficacy SMPN1 Right Kerinci Siak. self-efficacy has the greatest effect when compared with self-efficacy and to determine changes in performance in SMPN 1 Kerinci Kanan Kabupaten Siak, there is the influence of interpersonal communication teacher on teacher performance SMPN 1 Kerinci Kanan Kabupaten Siak, although the effect is not as big as the effect of which is owned by motivation , there is the influence of teachers' professional competence, self-efficacy, and interpersonal communication together on teacher performance SMPN 1 Kerinci Kanan Kabupaten Siak. teacher professional competence, self-efficacy, and interpersonal communication together contribute in determining the changes that occurred in the performance of teachers SMPN1 Right Kerinci Siak.Keywords: Teacher Professional Competence, Self Efficacy, Interpersonal Communication, Teachers Performance.